THE UNIVERSITY STUDENTS’ EXPERIENCES IN LEARNING ENGLISH USING YOUTUBE : A CASE STUDY OF INDEPENDENT LEARNING - Hendriwanto Hendriwanto; Tifani Dita Desela; Ramnita Saini Sharda (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2021)
YouTube is a website that facilitates users to share the videos they have, or just enjoy various videos uploaded by content creators. There are various kinds of videos that can be uploaded through this site, such as video blogs, music video clips, education videos, and others. Learning English independently through YouTube is a research topic which aims to find out the experiences of students while studying English and the challenges and opportunities they get. English Education in one private university in Cirebon became the object that the researcher chose and there were four female students who participants in this study. This research uses qualitative methods and data analysis uses thematic analysis. Data from this research is found by doing questionnaire and interview seasons. All participants showed positive responds. The results of this research indicate that YouTube is an application that can be used independently. Learning English by watching videos can help them improve their English skills, especially in listening and speaking skills. The benefits they get while using YouTube as a medium for learning English are interesting English learning content, good pronunciation, unfamiliar word, familiar with accent, a lot of information and knowledge through the videos that they see for learning.